MicroRNA-33 suppresses CCL2 expression in chondrocytes. Issue 3 (6th May 2016) - Wei, Meng; Xie, Qingyun; Zhu, Jun; Wang, Tao; Zhang, Fan; Cheng, Yue; Guo, Dongyang; Wang, Ying; Mo, Liweng; Wang, Shuai
Abstract : miR-33 suppresses CCL2 production via directly targeting its 3′UTR in the chondrocytes. The miR-33 /CCL2 axis in the chondrocytes regulates monocyte chemotaxis, providing a potential mechanism of macrophage infiltration in osteoarthritis (OA). Abstract : CCL2-mediated macrophage infiltration in articular tissues plays a pivotal role in the development of the osteoarthritis (OA). miRNAs regulate the onset and progression of diseases via controlling the expression of a series of genes. How the CCL2 gene was regulated by miRNAs was still not fully elucidated. In the present study, we demonstrated that the binding sites of miR-33 in the 3′UTR of CCL2 gene were conserved in human, mouse and rat species. By performing gain- or loss-of-function studies, we verified that miR-33 suppressed CCL2 expression in the mRNA and protein levels. We also found that miR-33 suppressed the CCL2 levels in the supernatant of cultured primary mouse chondrocytes. With reporter gene assay, we demonstrated that miR-33 targeted at AAUGCA in the 3′UTR of CCL2 gene. In transwell migration assays, we demonstrated that the conditional medium (CM) from miR-33 deficient chondrocytes potentiated the monocyte chemotaxis in a CCL2 dependent manner. Finally, we demonstrated that the level of miR-33 was decreased, whereas the CCL2 level was increased in the articular cartilage from the OA patients compared with the control group. In summary, we identified miR-33 as a novel suppressor of CCL2 in chondrocytes. The miR-33 /CCL2 axis in chondrocytes regulates monocyte chemotaxis, providing a potential mechanism of macrophage infiltration in OA.